Klinikopathologie der granulomatösen Entzündung: unter besonderer Berücksichtigung von Lunge und Zentralnervensystem = Clinical pathology of granulomatous inflammation : with special emphasis on the lungs and central nervous system - Tóth, Csaba (Der Radiologe, 2016)
Clinical issueGranulomatous diseases are not rare in routine daily diagnostics. Granulomas are an indication of a sufficiently functioning immune system. In the absence of granulomas, a possible immunodeficiency should also be considered (e.g. in tuberculosis) in the diagnostic procedure. Many types of diseases with different etiologies can cause granulomatous manifestations.DiagnosticsDiagnostic procedures should be oriented to the clinical symptoms and should include blood analyses, radiography, especially computed tomography (CT) and magnetic resonance imaging (MRI) and sampling for histology or cytology. In the case of proven granulomatous inflammation an infectious etiology should first be excluded. The diagnosis of a granulomatous disease should always be confirmed by histopathology when possible.AchievementsIn this study the origins and general histopathological classification of granulomatous diseases are presented. In addition to the most common granulomatous diseases, some special and rare forms are discussed, which should also be considered in the differential diagnostic process.Practical recommendationsThe diagnosis of a granulomatous disease should always be made in an interdisciplinary cooperation and requires close collaboration between radiologists, internists, pathologists and specialists in laboratory parameters.